Development of multi stage membrane distillation process : simulation and experimentation - Siddique, Istiaq Jamil (Kulliyyah of Enginering, International Islamic University Malaysia, 2018)
With the increased population, demand of fresh water supply is ever rising. Current desalination systems thus are challenged to meet this demand and their impact on nature is also questionable. Thus novel water treatment processes requiring the least amount of energy is of great importance. This scarcity of fresh water and availability of solar irradiation constitute the perfect condition for developing small scale solar waste water treatment plants. One of the emerging low energy process applicable is Membrane Distillation (MD). MD is a relatively lower temperature process which does not need to operate under high pressure like Reverse Osmosis (RO). A hydrophobic membrane maintains a barrier between hot feed water and coolant flowing outside. The vapour generated due to partial pressure difference crosses the pores of this hydrophobic membrane and travels toward the cooler side to condense and produce distillate. One of the biggest drawback in MD is polarization which increases the energy requirement and decreases the permeate flux. Hence, various methods have been applied to reduce this polarization. One simple way to reduce this polarization is by multi-staging. In this research polarization in single and multi-stage Air Gap Membrane Distillation (AGMD) was studied in detail. Momentum and energy equations were solved using finite difference method via COMSOL Multiphysics® to obtain the distribution of temperature at the interface for single stage and multi stage MD module. Polarization factors and permeate flux were calculated theoretically and these results were compared with the experimental values. Maximum deviation of 20% was found in the comparison and the most probable reasons were stated. Furthermore, feasibility of using soap-water/laundry water in MD was investigated. Also, performance of the multi stage MD module was analysed after coupling it to a solar collector. An average annual solar radiation of 1571 KWh/m2 was incorporated in the multi-stage MD system with a narrow air gap between the coolant and feed. It was observed that smaller sized multiple chambers can produce more distillate than a bigger sized chamber with a single large membrane. Finally, in contrast with the literature available, theoretical and experimental results proved that polarization was maximum at the mid portion of the membrane and when the mass transfer resistance imposed by the support was removed highest recorded value of 11.64 Kg/m2h permeate flux was obtained experimentally from a multi-stage module, while the single stage equivalent produced 10.4 Kg/m2h (At 50°C feed, 20°C coolant, 2 lpm flowrate, 20g/L salinity). This result is extremely high when compared with the literature as air gap in the module was 13mm while maximum permeate flux obtained (11 Kg/m2h) at these parameters had 2 mm air gap. The outcome of this research will enable making a theoretical model which can predict performance of MD for any configuration and flow conditions.